(RE)CONSTRUCTION OF THE EDUCATIONAL EXPERIENCE IN FUTURE TEACHERS’ VISIONS OF THEIR PROFESSIONAL ACTIVITY - Masiliauskienė, Erika; Lenkauskaitė, Jurgita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article presents the results of a scientific research obtained after the phenomenological content analysis of future teachers’ visions of their professional activity. In future teachers’ visions of their professional activity the representations of the (re)construction of the educational experience are clearly observed. The informants of the research reflecting on their experience of learning at school and the vision of their professional pedagogical activity reveal the content of pedagogical activity and its transformations. The article analyses how the person’s relationship to significant “others” constructs the knowledge about the teacher’s role. The “sub-world” of the educational experience, that is experienced and internalized by future teachers during the period of their learning at school and (re)constructed during their pedagogical studies is, in fact, an integral reality. Thus the (re)construction of the previously internalized educational experience is revealed as the new content of the educational experience arises. The results of the research permit to state that future teachers in the processes of the (re)construction of the educational experience do not demonstrate a strong identification with the internalized content of pedagogical activity/educational experience during their learning at school. The problem question of the research – what content of the educational experience at school do future teachers reflect on and how is the (re)constructed educational experience reflected on or recognized in the visions of professional activity.